EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK PEER GROUP DALAM MENINGKATKAN KEMAMP[UAN REMAJA MENJALIN HUBUNGAN PERSAHABATAN DI PANTI ASUHAN KHOIRIYAH HASYIM SURABAYA - Umi Anugerah Izzati, (Widya Cendika, 2011)
This research is done based on the phenomenon in which the teenagers have a lack of motivation to make a relationship with the others. The process how to make a relationship with the peers in Panti Asuhan environment. The purposes of the research are to know the effective the group guidance using peer groups in order to increase the teenagers capability to make a close relationship. Based on the effective test toward 40 teenagers in Panti Asuhan environment that is designed using pretest posttest one group design through t-test. It shows that peer group technique is very effective to make a close relationship in Panti Asuhan Khoiriyah Hasyim Surabaya.